Genetic diversity and virulence of novel sequence types of Streptococcus suis from diseased and healthy pigs in China - Wang, Shujie; Gao, Mingming; An, Tongqing; Liu, Yonggang; Jin, Jiamin; Wang, Gang; Jiang, Chenggang; Tu, Yabin; Hu, Shouping; Li, Jinsong; Wang, Jie; Zhou, Dongsheng; et al. (Frontiers in Microbiology, 2015)
Streptococcus suis is a serious threat to swine industry and public health. In this work, a total of 62 S. suis isolates recovered from infected and healthy pigs from four provinces in northern China were classified by multilocus sequence typing into nine sequence types (STs), including six novel ones, namely, ST417, ST418, ST419, ST420, ST421, and ST422. The majority (64.5%) of these 62 isolates belong to serotype 2; all of these serotype 2 isolates can be assigned into ST1 or ST28 clonal complex, indicating at least two parallel routes of clonal dissemination of these isolates. In these serotype 2 isolates, 23 (20 from healthy pigs and 3 from diseased pigs) were identified as ST7 strains, which were previously characterized as the cause of streptococcal toxic shock-like syndrome. The novel ST strains lack 89K pathogenicity island but can cause septicemia and meningitis in a mouse model, showing remarkable differences in virulence. The ST421 strain named HLB causes suppurative encephalitis. Our results highlighted the need for increased surveillance of S. suis in farm-raised pigs in northern China.